2017
DOI: 10.1080/10962247.2017.1310149
|View full text |Cite
|
Sign up to set email alerts
|

Future-year ozone prediction for the United States using updated models and inputs

Abstract: The relationship between emission reductions and changes in ozone can be studied using photochemical grid models, which are updated with new available information. This study was to update the previous Collet et al. studies by using the most current, at the time the study was done, models and inventory to conduct ozone source attribution and sensitivity studies. The source attribution results from this study provide useful information on the important source categories and provide some initial guidance on futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Fujita et al [34] in their study of source contributions of ozone precursors in California's South Coast Air Basin to ozone weekday and weekend variation showed that reduced NO x emission of weekend emission from motor vehicle caused higher level of ozone than during the weekday due to the higher ratio of NMHC (non-methane hydrocarbon) to NO x in this VOC-limited basin. Conversely, Collet et al [35] in their study of ozone source attribution and sensitivity analysis across the U.S showed that, in most of the locations, reduction in NO x emission is more effective than reduction in VOC emission in reducing ozone levels.…”
Section: Discussionmentioning
confidence: 92%
“…Fujita et al [34] in their study of source contributions of ozone precursors in California's South Coast Air Basin to ozone weekday and weekend variation showed that reduced NO x emission of weekend emission from motor vehicle caused higher level of ozone than during the weekday due to the higher ratio of NMHC (non-methane hydrocarbon) to NO x in this VOC-limited basin. Conversely, Collet et al [35] in their study of ozone source attribution and sensitivity analysis across the U.S showed that, in most of the locations, reduction in NO x emission is more effective than reduction in VOC emission in reducing ozone levels.…”
Section: Discussionmentioning
confidence: 92%
“…The modeling domain was the same as used in the CAMx source attribution study of Collet et al (2017). This domain, shown in Figure 1, is the 12US2 domain used by the EPA for its ozone assessment using the 2011based air quality modeling platform (EPA 2015).…”
Section: Modeling Approachmentioning
confidence: 99%
“…As in our previous CAMx source attribution study (Collet et al 2017), only the anthropogenic sectors from the 2011v6.2 platform were used and the natural source category emissions were developed. Emissions for the natural source categories were developed using the 2011 meteorological data and models for the 12 km (12US2) domain in a format suitable for CMAQ.…”
Section: Modeling Approachmentioning
confidence: 99%
See 2 more Smart Citations